The Publication of the Books by Adam Honory Kirkor in the Lithuanian Language during the Period of Lithuanian Press Ban Enforced by Imperial Russia (1864 ‒ 1904) - Kaunas, Domas (Knygotyra, 2018)
[full article and abstract in Lithuanian; abstract in English] Research into Adam Honory Kirkor’s life and work was initiated by a specialist in the history of Lithuanian culture, Michał Eustachy Brensztein, in his applied study Adam Honory Kirkor: Publisher, Editor and Vilnius Printer in 1834-67 (Adam Honory Kirkor. Wydawca, redaktor I właściciel drukarni w Wilnie od roku 1834 do 1867. Wilno, 1930). Presently his historiography has become internationally famous, and due to numerous publications in various languages it has branched out into the Polish, Lithuanian, and Belorusian trends. The Lithuanian trend was shaped by Kirkor’s liberal and compromise views recognizing the merits of historical Lithuania and the prospects of its continuity as well as by the reduced possibilities of research and cultural activities in the Polish-Lithuanian Commonwealth occupied by imperial Russia. The research and fact-finding works by Lithuanian researchers Reda Griškaitė, Antanas Kulakauskas, Pavel Lavrinets, Juozas Maceika, Zita Medišauskienė, Vytautas Merkys, Darius Staliūnas, and other authors in most cases analyze Kirkor’s attitude towards the Lithuanian national revival movement and his relations with the participants of this movement. In the article by the present author, research is oriented towards the adaptations, translations into Lithuanian and their publication in Lithuania Minor following the Lithuanian press ban in Greater Lithuania of three works by Kirkor: Grand Duke Vytautas (Beликiй князъ Витовтъ) published in a book by several authors Outlines of the History and Life of the Lithuanian People (Черты изъ исторiи и жизни литовскаго народа. Вильно, 1854); A Guide to Vilnius and Its Environs (Przewodnik po Wilnie i jego okolicach. Wilno, 1880); The Graves of Grand Dukes and Kings in Vilnius(Groby wielkoksiążęce i królewskie w Wilnie. Warszawa, 1882). A deeper insight is offered into the relationship between the author and the publishers and collaborators of the monthly Auszra that promoted the ideas of the Lithuanian national revival. The latter prepared the first Lithuanian translations of Kirkor’s works in conformity with the ideological aspirations of the Lithuanian nation in the new times. The sources of research were Kirkor’s books published in Polish and Lithuanian as well as the archival and published documents connected with the publishing process, and the bibliographical data accumulated by the bibliologists of several generations. Use is also made of the results of the assessment of the publishing organization and culture of Kirkor’s books established by the de visu method. In the course of research, a proposition is suggested that the need for Kirkor’s books felt by 19th-century Lithuanian society was programed in advance. The publishing of their Lithuanian translations in Tilsit (lit. Tilžė) and Bittehnen (lit. Bitėnai) accelerated the integration of Lithuanians in Lithuania Minor and Greater Lithuania and the civic rapprochement between the residents of old and new Lithuania, fostered their historical and national identity and promoted cultural variety and progress. Translated from the Lithuanian by Gražvydas Kirvaitis, Ph.D.